2009
DOI: 10.5713/ajas.2009.90073
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid in Rumen Fluid and Milk Fat, and Methane Emission of Lactating Goats Fed a Soybean Oil-based Diet Supplemented with Sodium Bicarbonate and Monensin

Abstract: A metabolic study was conducted with four ruminally-cannulated lactating goats (Saanen, 29 weeks lactation, 65± 5 kg) in a 4×4 Latin square design with 4 dietary treatments. The goats were fed a basal mixed diet consisting of 80% concentrate and 20% chopped rye grass hay (DM basis, CON). The goats were also fed the CON diet supplemented with soybean oil at a 5% level of the concentrate (SO), the SO diet supplemented with 0.5% of sodium bicarbonate (SO-B) or the SO-B diet supplemented with 30 ppm monensin (SO-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Monensin is the most studied ionophore and routinely used as an animal nutrition supplement [58]. Saanen goats supplemented with oils with sodium bicarbonate and monensin showed a shift in the production of molar concentrations of acetate to propionate, thereby reducing the production of CH 4 [59]. Furthermore, up to a 75% reduction in CH 4 production was observed on addition of 10% encapsulated fumarate to the diet without any negative effect on animal growth [58].…”
Section: Impact Of Heat Stress On Rumen Functionmentioning
confidence: 99%
“…Monensin is the most studied ionophore and routinely used as an animal nutrition supplement [58]. Saanen goats supplemented with oils with sodium bicarbonate and monensin showed a shift in the production of molar concentrations of acetate to propionate, thereby reducing the production of CH 4 [59]. Furthermore, up to a 75% reduction in CH 4 production was observed on addition of 10% encapsulated fumarate to the diet without any negative effect on animal growth [58].…”
Section: Impact Of Heat Stress On Rumen Functionmentioning
confidence: 99%
“…La inclusión dietaria de elevada cantidad de AS provoca que incremente la concentración del ácido graso C18:2 trans-10 cis-12 a nivel de biohidrogenación ruminal, el cual inhibe la enzima desaturasa-∆9 en la glándula mamaria y estimula una reducción en la síntesis de ácidos grasos de cadena corta y mediana, reflejándose en una caída en el contenido de grasa láctea (13) . Cabe mencionar que estos compuestos intermedios de la biohidrogenación del AS solamente influyen en el contenido de grasa, pero no en otros componentes del calostro, acorde a lo indicado por otros autores (27) .…”
Section: Producción Y Composición Del Calostrounclassified
“…[4][5][6] However, the occurrence of milk FA changes induced by dietary lipids would not be defined only by the activity of rumen bacteria, but should also take into account the time required by the FAs to leave the rumen, their absorption in the intestine, transportation to the mammary glands and subsequent incorporation to milk triglycerides. In this regard, studies with cannulated animals have demonstrated that the BH process is extremely quick, as well as that FAs absorbed in the duodenum can be observed in milk fat after 6 h. 7,8 Changes of milk FA contents after the inclusion of plant oils in the diet have been studied in cows, 9 ewes 10 and goats. 11,12 However, in most of those studies the milk sampling began 24 h after dietary supplementation.…”
Section: Introductionmentioning
confidence: 99%